2013
DOI: 10.1177/0969733012463721
|View full text |Cite
|
Sign up to set email alerts
|

The ethics of coercive treatment of people with dementia

Abstract: The aim of the present study was to describe how registered nurses in nursing homes ensure legal security, good and safe nursing care and uphold the dignity of nursing home residents with severe dementia without violating residents' integrity. Semi-structured interviews were conducted with 10 charge nurses in a county in central Sweden. The transcribed interviews were examined using manifest and latent content analyses. The manifest analysis identified actual local routines involving coercive treatment and reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 23 publications
0
24
0
1
Order By: Relevance
“…However, it should be noted that RNs are not always able to supervise other nursing staff due to time constraints (Mueller et al., ; Prentice & Black, ), and RNs are not always on duty. This should be taken seriously because insufficient gerontological nursing training and understaffing appears to preserve, for instance, the use of coercive treatment on people with dementia (Lejman, Westerbotn, Pöder, & Wadensten, ). A poor staffing skill mix may contribute to resident transfers from nursing homes to hospitals (Laging, Ford, Bauer, & Nay, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that RNs are not always able to supervise other nursing staff due to time constraints (Mueller et al., ; Prentice & Black, ), and RNs are not always on duty. This should be taken seriously because insufficient gerontological nursing training and understaffing appears to preserve, for instance, the use of coercive treatment on people with dementia (Lejman, Westerbotn, Pöder, & Wadensten, ). A poor staffing skill mix may contribute to resident transfers from nursing homes to hospitals (Laging, Ford, Bauer, & Nay, ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the right to integrity is clearly applicable to human beings that are not capable of autonomous decision making. Sometimes physical restraint is used in care, e.g., in the case of people with dementia, and even though autonomy might then not be an issue, there are still strong reasons to organize care so that the use of physical restraint is minimized, in order to be respectful of the integrity of persons (Lejman et al 2013).…”
Section: Human Rights and Respect For Personsmentioning
confidence: 99%
“…The studies also revealed research demands in the field of elderly-centered care. It is necessary to understand how this approach can help to reduce physical restrictions in the institutionalized elderly (45) , to establish a stronger relationship between elderly-centered care and increased quality of care (44) , and to find ways to ensure the implementation of existing strategies (14) .…”
Section: Elderly Care Modelmentioning
confidence: 99%